A clinical case study of the use of ecological momentary assessment in obsessive compulsive disorder - Tilley, Peter; Rees, Clare (Frontiers Research Foundation, 2014)
Accurate assessment of obsessions and compulsions is a crucial step in treatment planning for Obsessive-Compulsive Disorder (OCD). In this clinical case study, we sought to determine if the use of Ecological Momentary Assessment (EMA) could provide additional symptom information beyond that captured during standard assessment of OCD. We studied three adults diagnosed with OCD and compared the number and types of obsessions and compulsions captured using the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) compared to EMA. Following completion of the Y-BOCS interview, participants then recorded their OCD symptoms into a digital voice recorder across a 12-h period in reply to randomly sent mobile phone SMS prompts. The EMA approach yielded a lower number of symptoms of obsessions and compulsions than the Y-BOCS but produced additional types of obsessions and compulsions not previously identified by the Y-BOCS. We conclude that the EMA-OCD procedure may represent a worthy addition to the suite of assessment tools used when working with clients who have OCD. Further research with larger samples is required to strengthen this conclusion.